Establishment and Validation of LC-MS/MS Technique for Pafolacianine Quantification in Rat Plasma, with Application to Pharmacokinetic Assessment - Pilli, Sandhya; Kalakonda, Sri Nataraj; Rajendran, Vijayalakshmi (Indian Journal of Pharmaceutical Education and Research, 2024)
Background: Establishing and validating a sensitive and accurate LC-MS method for quantifying pafolacianine in rat plasma was the primary objective of this study. Phenylalanine was used as the internal standard, and the validation procedure adhered to the protocols specified by the Food and Drug Administration of the United States. Materials and Methods: This article presents an overview of the bioanalytical LC-MS method, utilizing an Inertsil ODS column (150 mm x 4.6 mm, 3.5 μm) and an organic mobile phase comprising acetonitrile and 0.1% formic acid buffer in a ratio of 40:60. Results: The calibration curve for pafolacianine exhibited a linearity range of 5-100 ng/mL (r2=0.9999). Liquid-liquid extraction was employed to recover pafolacianine from rat plasma, resulting in recovery percentages of 100%, 99.7%, and 99.8% at three different concentration levels. Pafolacianine remained stable during storage under various conditions (three freeze-thaw cycles, benchtop, autosampler, short-term, and long-term storage). Pharmacokinetic analysis yielded key parameters, including a half-life of 9.6 m and a time to reach a maximum concentration of 5 m. Pafolacianine and phenylalanine were identified using proton adducts in the LC-MS analysis at m/z 1326.3/574.6 and 166.08/144.8, respectively, by employing positive mode multiple reaction monitoring. Conclusion: This comprehensive evaluation demonstrates that the method meets stringent criteria for system specificity, linearity, and accuracy, all well within the predefined acceptance limits. Its adaptability for the precise determination of pafolacianine positions it as an invaluable tool in the field of bioanalysis, expanding its clinical utility.
Keywords: Pafolacianine; Phenylalanine; Pharmacokinetics; Bio-analytical; Rat plasma; LC-MS/; MS